2022
DOI: 10.1111/cdoe.12796
|View full text |Cite
|
Sign up to set email alerts
|

Are there more women in the dentist workforce? Using an intersectionality lens to explore the feminization of the dentist workforce in the UK and US

Abstract: In this paper, we seek to understand feminization of the dentist workforce moving beyond previous research that has looked at gender in isolation. We contend that little consideration has been given to how gender interacts with other important social identities such as race/ethnicity to influence the opportunities and barriers that female dentists encounter during their dental career. We argue that the scholarly debate about the feminization of the dentistry has not acknowledged the intersectionality of women'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It is important to remember that the feminization of Dentistry was directly linked to the trajectory of the feminist movement, which began with the struggle for more egalitarian relationships for women and later served as a motto for the development of other causes, highlighting racism and LGBTQ+ phobia and the hegemony of CIS heteronormative bodies. [33][34][35][36][37][38][39][40][41][42][43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to remember that the feminization of Dentistry was directly linked to the trajectory of the feminist movement, which began with the struggle for more egalitarian relationships for women and later served as a motto for the development of other causes, highlighting racism and LGBTQ+ phobia and the hegemony of CIS heteronormative bodies. [33][34][35][36][37][38][39][40][41][42][43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dental schools coordinated by women (when compared with men) were 2.13 times more likely to develop pedagogical strategies with the aim of caring for the oral health of the LGBTQ+ population. It is important to remember that the feminization of Dentistry was directly linked to the trajectory of the feminist movement, which began with the struggle for more egalitarian relationships for women and later served as a motto for the development of other causes, highlighting racism and LGBTQ+ phobia and the hegemony of CIS heteronormative bodies 33–46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggests that most graduates of DH in Europe will continue to be female; however, male numbers may be increasing compared to previous estimates. Two recent narratives uncovered existing inequalities in the oral health workforce that have persisted irrespective of the increase in female OHPs, particularly across different ethnic groups 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…As has been widely reported, this might be due to a lack of women practicing dentistry, who can also serve as role models for the future generation. Indeed, it is reported that when a woman takes on a leadership position in dentistry, she has less probability of being married or with children [ 3 , 4 , 5 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This scenario frightens new generations of young women who see themselves as forced to choose between a career or family, which is a scenario that young men do not perceive [ 26 ].…”
Section: Discussionmentioning
confidence: 99%